Application of cryopreserved placental polypeptide complex in murine acubarotrauma model - Salnykov, Dmytro; Skoryk, Anastasiya; Shevchenko, Mariia; Shcheniavskyi, Ivan; Chub, Oleg; Voitenko, Stanislav; Osetsky, Oleksandr; Prokopiuk, Olga (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):250